The Effect of secretome-hypoxia mesenchymal-stem-cells and vitamin-d3 in type-2 diabetes-mellitus induced periodontitis rats - Muchaeroni, Isa Anshori; Rochmah, Yayun Siti; Putra, Agung (Odonto : Dental Journal, 2023)
Background: A systemic metabolic disorder by insulin resistance, type-2 diabetes mellitus (T2DM), is characterised by an increased level of reactive oxygen species (ROS) and decreased superoxide dismutase (SOD), which is associated with the activation of proinflammatory cytokine pathways such as tumor necrosis (TNF)-Î±. This condition usually stimulates inflammation of the periodontal tissue (periodontitis). Vitamin-D3 can inhibit the release of inflammatory mediator and reduce the risk of chronic periodontitis. Purpose this study to determine the effect of the secretome-hypoxia mesenchymal-stem-cells (SH-MSCs)-Vitamin-D3 combination on the expression of SOD, IL-10, and TNF-Î± genes in T2DM periodontitis-induced rats. Method: 30 rats were randomly divided into five groups; normal sham condition, positive control, SH-MSCs group, vitamin-D3 group, and combination of SH-MSCs and vitamin D3 group. SH-MSCs were injected at doses of 150 uL in the gingival. In addition, vitamin D3 5000 IU 2.25 mcg were administrated orally. After 35 days, all rats were sacrificed, and qRT-PCR from gingival tissue was performed to identify the expression of SOD, IL-10 and TNF-Î± genes Results: The results a significant increase in SOD and IL-10 gene expression (p